Immunostaining for hepatitis B viral antigens in liver: Association with clinical, biochemical, and virologic features of disease - Kleiner, David E; Lisker‐Melman, Mauricio; Wahed, Abdus S; Bhan, Atul K; Nalesnik, Michael A; Choi, Eun‐Young K; Leonard, Kelsey K; Ghany, Marc G; Chung, Raymond T; Di Bisceglie, Adrian M; Lau, Daryl T‐Y; Roberts, Lewis R; et al. (Journal of gastroenterology and hepatology, 2023)
Background and Aim Staining for hepatitis B viral antigens is often done in liver biopsies from patients with chronic hepatitis B, but its correlates with clinical phenotypes are not well described. Methods Biopsies were collected from a large cohort of adults and children with chronic hepatitis B viral infection through the Hepatitis B Research Network. Immunohistochemical staining of sections was done for hepatitis B surface antigen (HBsAg) and hepatitis B core antigen (HBcAg) and then centrally read by the pathology committee. The degree of liver injury and pattern of staining were then correlated with clinical characteristics, including the clinical phenotype of hepatitis B. Results Biopsies from 467 subjects were studied, including 46 from children. Immunostaining for HBsAg was positive in 417 (90%) with scattered hepatocyte staining being the most common pattern. HBsAg staining correlated best with serum levels of HBsAg and hepatitis B viral DNA; the absence of HBsAg staining was often a prelude to loss of HBsAg from serum. HBcAg staining was positive in 225 (49%), and, while cytoplasmic staining was more frequent than nuclear staining, both nuclear and cytoplasmic positivity were often seen in the same specimen. Staining for HBcAg correlated with both level of viremia and liver injury. No biopsies from inactive carriers had stainable HBcAg, while 91% of the biopsies from those with hepatitis B e antigen‐positive chronic hepatitis B stained positively for HBcAg. Conclusion Immunostaining for hepatitis B viral antigens may yield helpful insights into liver disease pathogenesis but appears to add little to commonly used serological and biochemical blood tests.